Comparison of Merriam's Turkey Harvest Strategies and Survival in Northern Arizona. (23rd February 2020) - McCall, Thomas C.; Clement, Matthew J.; Wakeling, Brian F.
Abstract : We compared annual survival and hunting‐related mortality of female Merriam's turkeys in northern Arizona between 2 time periods to determine how regulation changes affected hunting opportunity. The decision to restrict fall turkey hunting opportunities using a regulated permit system had little effect on female turkey survival and hunting‐related mortality, but reduced the number of turkey hunters that could participate by 43%. ABSTRACT: We compared annual survival and hunting‐related mortality of female Merriam's turkey ( Meleagris gallopavo merriami ) between a period of relatively liberal hunting regulation (before 1990) and after implementation of a more conservative hunting regulation (after 1991) in Arizona, USA, to determine how those regulation changes affected hunting opportunity. Between January 2013 and October 2016, we used radiotelemetry to estimate survival and mortality rates of 185 female wild turkeys (60 juvenile, 125 adult) on 3 study areas in northern Arizona, which we compared with survival and mortality rates documented during an earlier study (1987–1990; Wakeling 1991). We used the nest survival approach in Program MARK to estimate survival and mortality rates for turkeys. Annual survival rate for radiomarked hens was 0.649 (95% CI = 0.597–0.702). Annual survival differed among Game Management Units, but not by season, year, age, or age × season interaction. Harvest rates were 0.024 (95% CI = 0.011–0.51) and 0.039 (95% CI = 0.022–0.071) for females during spring (Mar–May) and fall (Aug–Oct), respectively. The overall human‐caused mortality rate (i.e., fall harvest, spring harvest, unlawful take, wounding loss) was 0.073 (95% CI = 0.046–0.115). The decision to restrict fall turkey hunting opportunities using a regulated permit system had little effect on female turkey survival and hunting‐related mortality, but reduced the number of turkey hunters that could participate by 43%. © 2020 The Wildlife Society.